2021
DOI: 10.3389/fphar.2021.684898
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of High-Content Complex Dietary Fiber in Medical Nutrition Therapy for Gestational Diabetes Mellitus

Abstract: Objectives: A controlled open clinical study was conducted to evaluate the role of Ricnoat, a high-content complex dietary fiber powder produced by Zhuhai Aimed Biotechnology Co. Ltd., in medical nutrition therapy (MNT) to treat gestational diabetes mellitus (GDM). The study aimed to investigate glycemic control, lipid control, weight control, and pregnancy outcomes (neonatal weight) in patients with GDM, as well as evaluate the clinical safety of Ricnoat.Methods: A total of 120 patients with GDM who were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…We found that CRD intervention can significantly reduce the incidence of an abnormal LDLC level in the middle of GDM pregnancy. This study preliminarily confirmed that CRD pattern plays a certain role in the improvement of the LDLC level of GDM in the second trimester, which is consistent with a series of studies that found that specific forms of MNT intervention can improve lipid metabolism, control weight gain during pregnancy and improve pregnancy outcomes [34].…”
Section: Discussionsupporting
confidence: 90%
“…We found that CRD intervention can significantly reduce the incidence of an abnormal LDLC level in the middle of GDM pregnancy. This study preliminarily confirmed that CRD pattern plays a certain role in the improvement of the LDLC level of GDM in the second trimester, which is consistent with a series of studies that found that specific forms of MNT intervention can improve lipid metabolism, control weight gain during pregnancy and improve pregnancy outcomes [34].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, when the system collects data, the commonly used data are collected once a day; the less commonly used data are collected once a week or a month. The collection time is set in the evening when there are almost no patients visiting a doctor, no medical staff operating the information system, and it is more suitable to collect data when the data is not updated [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…GDM during pregnancy might lead to a high tendency of congenital malformations, including the heart, digestive system, and nervous system. Lifestyle and pharmacological interventions have brought about beneficial outcomes in the prognosis in GDM (Wang et al, 2021). In this study, a rat model of GDM was successfully established, and the OD treatment reduced the levels of blood glucose and inflammation, and alleviated insulin secretion and pancreatic tissue damage through AMPK pathway in GDM rats.…”
Section: Discussionmentioning
confidence: 98%